THE EFFECT OF ZOOM APP TOWARDS STUDENTS' INTEREST IN LEARNING ON ONLINE LEARNING - Kasman Kasman; Zohri Hamdani (Dinasti International Journal of Education Management And Social Science, 2021)
This study was to know the effect of zoom app towards students' interest in learning. The population used in this study were 496 students majoring in Islamic Religious Education of STAIN Mandailing Natal. There were 38 students of the Department of Islamic Education to be sampled in this study. Data collection techniques that researchers use include questionnaires, pretest, posttest, and interviews The analysis data used the SPSS 16 program to determine the data tabulation and qualitative descriptive. The result of this study shown that there is an increased students' interest in learning by using zoom app as a learning modality during a pandemic. The use of it is proven to have a significant effect on students' enthusiasm for learning so that there is an increasing in students' interest in learning.